Peran Komunikasi Persuasif Dalam Media Sosial - Setya Prihatining Tyas; Nazlah Azzahra; Bernika Meilani Ifada; Noerma Kurnia Fajarwati (STIKes Ibnu Sina Ajibarang, 2024)
Social Media, as a growing persuasive communication environment, provides space for different types of persuasive communication that influence ideas, perception, and dissemination of information. Social Media, as an online platform with fast messaging speeds, is shaping a new communication landscape. In its development closely linked to communication technologies, social media provided a space for users to share ideas and information, creating virtual communities. Despite providing advantages such as marketing and global interaction, social media has also come under criticism for the spread of false information and negative social phenomena. This study used qualitative analysis method with primary data obtained from textbooks, journals, and documents, while secondary data were analyzed through content analysis. Social Media is becoming an important tool in the context of politics, by influencing digital literacy, political education, public opinion, raising support, and developing political communication skills. In terms of information dissemination, persuasive communication on social media can shape opinions through social campaigns and persuasive messages. social media has changed the way we communicate, shape opinions, and influence behavior. Persuasive communication plays a central role in shaping collective narratives, influencing ideas, and driving action. In the complexities of social media, managing persuasive communication ethically is key to achieving positive impact.